a Designing Ergonomic Seating for Stone Bara Songket Woven Fabric Craftsmen as an Effort to Reduce Mosculeskeletal Complaints Using Rapid Entire Body Assessment (Reba) at Umkm Rumah Songket Maisyarah - Gani, Subhan A.; Erliana, Cut Ita; Lia, Julia Diyanti (TALENTA Publisher, 2025)
UMKM Rumah Songket Maisyarah is one of the micro, small, and medium enterprises in the field of songket weaving. The process of making songket fabric still uses Alat Tenun Bukan Mesin (ATBM) with seating consisting of simple boards without cushions or backrests. The weavers for 8 hours a day in a sitting posture. Based on the results of the Nordic Body Map questionnaire distribution, it was found that the weavers complained of pain in the back, shoulders, waist, buttocks, thighs, and calves. If this is left untreated for a long time, it will result in weavers suffering from musculoskeletal disorders. The purpose of this research is to assess the work posture and propose an ergonomic seating arrangement for weavers to reduce the risk of musculoskeletal disorders. The method used in this research is Rapid Entire Body Assessment. The results of the posture assessment show that the weavers are at a high level of musculoskeletal risk. The researchers proposed the design of a songket weaving seat that aligns with the anthropometric data of the weavers, with a seat height of 47.1 cm, a seat depth of 48.65 cm, a seat length of 100 cm, a backrest height of 59.9 cm, a backrest length of 100 cm; and seat and backrest thickness of 4 cm. It is hoped that this proposal can reduce the risk of musculoskeletal disorders among songket weavers in Batu Bara.